Effects of adding scapular stabilization exercises to a periscapular strengthening exercise program in patients with subacromial pain syndrome: A randomized controlled trial. (October 2020) - Hotta, Gisele Harumi; Gomes de Assis Couto, Amanda; Cools, Ann M.; McQuade, Kevin James; Siriani de Oliveira, Anamaria
Abstract: Background: Interventions focused on the scapula should be considered in treating subacromial pain syndrome (SAPS). However, the effect of adding scapular stabilization exercises to protocols of progressive strengthening of the shoulder complex muscles on a non-multimodal approach remains unclear. Objective: To investigate the effect of adding scapular stabilization exercises, emphasizing retraction, and depression of the scapula, to a progressive periscapular strengthening protocol on disability, pain, muscle strength, and ROM in patients with SAPS. Design: Randomized, controlled, superiority trial, prospectively registered, two-arms, parallel, blind assessor, blind patient, and allocation concealment. Methods: Sixty patients with SAPS were randomly allocated into two groups: Periscapular Strengthening (PSG) or Scapular Stabilization (SSG) exercises. The interventions were performed three times a week for eight weeks. The primary outcome function and secondary outcomes (Pain, kinesiophobia, global perceived effect, satisfaction with treatment, the range of motion, scapula position and muscle strength) were measured in the baseline, four weeks, eight weeks (end of intervention) and 16 weeks after baseline. Shoulder pain and function were assessed by the Brazilian version of the Shoulder Pain and Disability Index (SPADI-Br). Results: A total of 60 patients were included and randomized to PSG (n = 30) or SSG (n = 30) from March 2016 to June 2017. There were no between group differences in primary and secondary outcomes at any time point. Conclusion: The inclusion of the isolated scapular stabilization exercises, emphasizing retraction and depression of the scapula, to a progressive general periscapular strengthening protocol did not add benefits to self-reported shoulder pain and disability, muscle strength, and ROM in patients with SAPS. Trial registration: ClinicalTrials.gov. Highlights: Effect of adding scapular stabilization exercises to a strength training was evaluated. Scapular stabilization exercise emphasized retraction and depression of the scapula. Scapula stabilization do not add benefits to shoulder function and pain. Scapula stabilization do not add benefits to range of motion and muscle strength.